Forming an Effective Strategic Management System - Irada ABDULLAYEVA; Sevil MUSAYEVA; Aytakin MAMMADOVA (Communications of International Proceedings, 2021)
The article discusses the company's strategy - as a single system, proceeding from the goals and expected results of the company as a whole and reaching the goals and results of each department, each employee, and vice versa - from individual results to the result of the company as a whole. Any company exists in a dynamically changing environment, and a strategy is just what is needed in order to build the company’s activities in accordance with long-term general plans and current specific plans, with a specific current situation, with specific private results achieved at lower levels, strategy correction depending on the particular results achieved and the situation. Clear policies adopted by the team play a significant role in the effectiveness of the ongoing strategy. For example, one of the consulting companies set its policy not to work with companies involved in alcohol and tobacco - this limited the circle of its potential customers, excluded very profitable customers, this of course limited the current economic efficiency of the company, but raised the social efficiency that the company puts above current momentary results, which will enhance the image of the company, and which, in the future, will lead to increased economic efficiency. Politicians do not just limit and direct the activities of the organization, they reduce possible alternatives to activities in a visible space where you can monitor and analyze and choose the most effective.
Keywords: Strategic Management; Efficiency; Financial Stability; Goal Setting.